Expression of a dominant‐negative AtNEET‐H89C protein disrupts iron–sulfur metabolism and iron homeostasis in Arabidopsis. (9th December 2019) - Zandalinas, Sara I.; Song, Luhua; Sengupta, Soham; McInturf, Samuel A.; Grant, DeAna G.; Marjault, Henri‐Baptiste; Castro‐Guerrero, Norma A.; Burks, David; Azad, Rajeev K.; Mendoza‐Cozatl, David G.; Nechushtai, Rachel; Mittler, Ron
Summary: Iron–sulfur (Fe–S) clusters play an essential role in plants as protein cofactors mediating diverse electron transfer reactions. Because they can react with oxygen to form reactive oxygen species (ROS) and inflict cellular damage, the biogenesis of Fe–S clusters is highly regulated. A recently discovered group of 2Fe–2S proteins, termed NEET proteins, was proposed to coordinate Fe–S, Fe and ROS homeostasis in mammalian cells. Here we report that disrupting the function of AtNEET, the sole member of the NEET protein family in Arabidopsis thaliana, triggers leaf‐associated Fe–S‐ and Fe‐deficiency responses, elevated Fe content in chloroplasts (1.2–1.5‐fold), chlorosis, structural damage to chloroplasts and a high seedling mortality rate. Our findings suggest that disrupting AtNEET function disrupts the transfer of 2Fe–2S clusters from the chloroplastic 2Fe–2S biogenesis pathway to different cytosolic and chloroplastic Fe–S proteins, as well as to the cytosolic Fe–S biogenesis system, and that uncoupling this process triggers leaf‐associated Fe–S‐ and Fe‐deficiency responses that result in Fe over‐accumulation in chloroplasts and enhanced ROS accumulation. We further show that AtNEET transfers its 2Fe–2S clusters to DRE2, a key protein of the cytosolic Fe–S biogenesis system, and propose that the availability of 2Fe–2S clusters in the chloroplast and cytosol is linked to Fe homeostasis in plants. Significance Statement: Orchestrating iron–sulfur cluster biogenesis, iron availability and reactive oxygen levels is a major challenge to plants that generates considerable quantities of atmospheric oxygen within their chloroplasts. Disrupting AtNEET function in Arabidopsis uncoupled iron–sulfur metabolism between the chloroplast and the cytosol, resulting in elevated iron content, chlorosis, structural damage to chloroplasts and a high seedling mortality rate.